2019
DOI: 10.18699/vj18.441
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease activity as a new prospective disease resistance marker in potato

Abstract: Disease resistance is an important characteristic for each variety of potato, and the search for pathogen resistance markers is one of the primary tasks of plant breeding. Higher plants possess a wide spectrum of enzymes catalyzing the hydrolysis of nucleic acids; it is believed that protection against pathogens is the most probable function of the enzymes. RNases are actively involved in several immune systems of higher plants, for example, systemic acquired resistance (SAR) and genetic silencing, hence RNase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…It should be noted that the ribonuclease activity decreased in the PVY-susceptible VS variety and increased in the PVY-resistant Ural variety (Figure 4). Our results are consistent with the data obtained by other authors, in which a high correlation was found between the ribonuclease activity and the resistance to viruses in different potato varieties [26].…”
Section: Antiviral Activity Of the Endophytic Strains B Subtilis 26d ...supporting
confidence: 94%
“…It should be noted that the ribonuclease activity decreased in the PVY-susceptible VS variety and increased in the PVY-resistant Ural variety (Figure 4). Our results are consistent with the data obtained by other authors, in which a high correlation was found between the ribonuclease activity and the resistance to viruses in different potato varieties [26].…”
Section: Antiviral Activity Of the Endophytic Strains B Subtilis 26d ...supporting
confidence: 94%
“…Thus, for buckwheat varieties Roksolana and Kara-Dag with different resistance to the buckwheat burn virus (BBV), a positive correlation between resistance to virus and RNase activity was shown ( Sindarovska et al, 2014 ). Trifonova et al (2018) have proposed to use the level of RNase activity in potato leaves as a selective marker for resistance to viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas putida A3 ( Yang et al, 2012 ) and B. pumilus 7P/3-19 ( Sharipova et al, 2015 ) were shown to cleave viral particles in the juice from TMV-infected tobacco plants. The strong positive correlation was shown between the RNase activity in different potato varieties and their resistance to PVX, PVY, PVM, and PVS ( Trifonova et al, 2018 ). Expression of RNase gene PAC1 from Schizosaccharomyces pombe in soybean plants led to a significantly higher level of uninfected with prevalent in soybean-growing regions of China soybean mosaic virus (SMV) SC3 strain under the field conditions, compared with the areas where non-transformed plants were grown ( Yang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest to develop antiviral biocontrol agents based on PGPR isolates having high RNase activity or the preparation of RNase itself to protect plants from viral infection, taking into account that the majority of phytoviruses are RNA viruses (Sharipova et al, 2015) as well as the generation of genetically modified plants expressing RNase genes (Trifonova et al, 2004). It has been found that potato plants expressing Serratia marcescens nuclease display enhanced resistance to pathogens (Trifonova et al, 2018).…”
Section: Discussionmentioning
confidence: 99%